Bio-based composites from plant based precursors and hydroxyapatite with shape-memory capability. (7th July 2020) - Wong, Tuck-Whye; Behl, Marc; Syazana Mohd Yusoff, Noor Izyan; Li, Tiefeng; Wahit, Mat Uzir; Ismail, Ahmad Fauzi; Zhao, Qian; Lendlein, Andreas
Abstract: A series of bio-based composites consisting of degradable thermoset poly[xylitol-(1, 12-dodecanedioate)] (PXD) and hydroxyapatite microparticles (HA) was prepared. Equimolar amounts of xylitol and 1, 12-dodecanedioic acid were reacted under catalyst-free polyesterification and the synthesized composites (PXDHC y ) consist HA particles ranging between 0 wt% and 20 wt%. Crystallinity of the polymer matrix decreased at low content of HA (5 wt%) as the microparticles hindered crystallization of 1, 12-dodecanedioate segment and then increased when the content of HA was raised (from 10 wt% to 20 wt%) as the polymer chains crystallized on surface of microparticles. All PXD and PXDHC y are able to hydrolytically degrade with around 7 wt% to 20 wt% mass loss after 16 weeks incubation in water (rate depends on HA content). The capability of PXD and PXDHC y composites to keep a temporary shape after a deformation process correlated with the polymer crystallinity whereas the shape recovery was 99%. The switching temperatures of PXD and PXDHC y composites ranged around 50 °C (and correlated to the melting-transition temperature) and did not vary with the loading of HA. A prototype of PXDHC y composite smart fixation plug was demonstrated and showed excellent potential to be used as bio-based fixation device for household appliances. Graphical abstract: Image 1